Prosthetic valve endocarditis: a review of 24 cases - Petheram, Ian S. (1977)
Petheram, I. S. and Boyce, J. M. H. (1977).Thorax, 32, 478-485. Prosthetic valve endocarditis: a review of 24 cases. Twenty-four episodes of prosthetic valve endocarditis occurred in 23 patients in a 10-year period. Fifteen patients presented within four months and nine from 14 months to seven years after surgery. The commonest pathogens in the early group were Candida albicans (five), but in three of these patients other organisms were found; diphtheroid species in five and Staphylococcus aureus in three. Four patients in the late group had Streptococcus viridans infection. Antistaphylococcal operative prophylaxis has been successful, but opportunist organisms of low virulence in health have emerged as pathogens. Continuous monitoring of antibiotic prophylaxis may reduce the incidence of early cases, and antibiotic cover for dental procedures should be as meticulous after valve replacement as before operation. The most frequent cause of death in both groups was delayed or inadequate treatment because of failure to isolate the pathogens from blood cultures with consequent severe haemodynamic upset or uncontrolled infection. Previous courses of antibiotics were the usual reason for negative blood cultures. Successful management requires close liaison with an interested clinical bacteriologist and aggressive surgery for haemodynamic faults or failure to control infection.